Pelatihan Pengelolaan Limbah Medis Rumah Tangga di Perumahan Home Bekonang Sentul RT 02 RW 7 Mojolaban Sukoharjo - Hanik, Nur Rokhimah; Wiharti, Tri; Nisaa, Arifatun; Nugroho, Anwari Adi; Saputra, Dian Andhi; Mardyah, Muthia; Armania, Vallery (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This Community Service Program responds to the increasing volume of household medical waste, such as disposable masks, diapers, syringes, and expired medicines, which are often disposed of carelessly and pollute the environment. The partners are located in the Home Mojolaban Sentul housing complex RT 02 RW 7 Mojolaban Sukoharjo, which is a new housing complex, with 30 young couples and many toddlers who often have problems with medical waste. The objectives of this program include educating the community about medical waste, the dangers of medical waste, and how to sort medical waste. The activities designed and implemented include socialization and training on sorting and managing medical waste. From the results of counseling and training on managing household medical waste for residents of the Home Bekonang Sentul housing complex, it can be concluded; There was an increase in understanding about managing household medical waste from an average score of 68.5 to 89.58, meaning there was an increase in understanding of 21.08 (35.47%). For waste sorting skills, all participants are skilled because the average score is 97. Household Medical Waste Management Training Activities and the like still need to be implemented and improved, because they have many benefits for improving public welfare and health.